MENINGKATKAN KEMAMPUAN MEMBACA SUKU KATA TERBUKA MELALUI PERMAINAN FASHION SHOW ALFABET PADA ANAK TKIT AL-MADINAH - Andri Asih, Ayu; Dudin Abdul Latip, Asep; Zulvian Iskandar, Yogha (Penerbit Lafadz Jaya, 2025)
The ability to read syllables in group B of TKIT AL-Madinah is still not optimal, this is the due to a lack of learning inovation that causes children to feel bored. This study aims to determine the improvement of the ability to read open syllables in group B of TKIT Al-Madinah before and after using the alphabeth fashion show game and to find out the steps of the alphabet fashion show game in learning to read open syllables in group B TKIT Al-Madinah. The research method used in the study is the Classroom Action Research (PTK) method which is cerried out in 2 cycles each consisting of 3 meetings. The subject of this study is 13 students of group B TKIT Al-Madinah. The results of this study show alphabet ware able to improve the ability to read open syllables in group B children TKIT Al-Madinah. The evidenced by the result of the persentage of chidren who reach the minimum category of development (BSH) increaed 15% in the pre cycle, to 30% in the first cycle and finally reaching 77% in the second cycle. Thus, the alphabet fashion show game is an effective game in improving the ability to read open syllablesin children.